Sistem Keamanan Pintu dan Jendela Rumah Berbasih IoT - Kurniasih, Wahyuni; Rakhman, Abdul; Salamah, Irma (STIKOM Tunas Bangsa Pematangsiantar, 2020)
The house is the most valuable asset, therefore security at home is also very important. Therefore a home security system is created that combines a microcontroller with an Android smartphone application. The microcontroller used is the Raspberry Pi which is equipped with a camera as a home security monitoring system and various sensors as detectors such as magnetic, PIR sensors and solenoids as automatic door locks. So if the sensors that are installed detect something at home, then the homeowner will immediately get a notification sent by the database to the smartphone application, and the homeowner can monitor the state of the house right then through photos and videos recorded by cameras that have been installed at home.